Pengaruh Kualitas Pelayanan dan Persepsi Harga Terhadap Loyalitas Pelanggan (Pada Alfamart Simogunung Surabaya) - Dika Bayu Saputra; Pribanus Wantara (Management Department of Economics and Business Of Trunojoyo Madura University, 2022)
This research aims to determine the effect of service quality, price perception on customer loyalty with a case study on Alfamart consumers in Simo Gunung, Surabaya. The research method used is a quantitative method with primary data through questionnaires distributed to respondents. The sampling technique in this study used a simple random sampling technique, namely sampling from the population was carried out randomly without paying attention to the existing strata in the population, which then obtained 96 samples.The results obtained from the research conducted indicate that service quality has a significant and significant effect on customer loyalty as well as price perceptions have a significant effect on customer loyalty. And simultaneously service quality and price perceptions have a positive effect on customer loyalty variables simultaneously